Exploring and understanding the scope and value of the Parkinson's nurse in the UK (The USP Project): a realist economic evaluation protocol. Issue 10 (16th October 2020) - Brown, Sarah; Dalkin, Sonia Michelle; Bate, Angela; Bradford, Russ; Allen, Charlotte; Brittain, Katie; Clarke, Amanda; Hand, Annette
Abstract : Introduction: There are multiple configurations of specialist nurses working in the field of Parkinson's. Parkinson's Nurse Specialists (PNSs) are recognised as playing a pivotal role; however, there is little published evidence to demonstrate their effectiveness. Further evidence is needed to establish which aspects of the PNSs provide the greatest benefit to people with Parkinson's and their families, and the cost-effectiveness of different models of care. Methods and analysis: Realist approaches explain how and why programmes work (or not) through striving to answer the question: what works, for whom and under what circumstances. This research uses a realist evaluation and aims to integrate an economic analysis within the realist framework. We refer to this as 'realist economic evaluation'. It comprises four phases: (1) developing resource-sensitive initial programme theories (IPTs) using surveys to gain a better understanding of the role and impact (costs and benefits) of the PNSs; (2) testing the IPTs through qualitative interviews and quantitative data analysis; (3) evaluating the cost and resource use implications alongside the benefits associated with the role of the PNSs and (4) iteratively refining the IPTs throughout the project. The IPTs will draw on both quantitative and qualitative data. The result of the study will be a series of refined programme theories, which will explain how specialist nurses work in the field of Parkinson's in the UK, what impact they have on people with Parkinson's and their families and carers, and at what cost. Ethics and dissemination: Northumbria University, the Health Research Authority and Health and Care Research Wales have approved this study. Key findings will be disseminated throughout the duration of the project online and through social media, and via annual and regional Parkinson's meetings and the Parkinson's UK Excellence Network. Academic dissemination will occur through publication and conference presentations.